The Behavior of Listeria monocytogenes During the Shelf Life of Wiener Sausages, as an Effect of Fermented Parsley Root Juice and Hawthorn Berry Phenolics - Georgeta Ștefan; Gheorghe Valentin Goran; Corina Nicoleta Predescu; Maria Rodica Gurău; Stelian Bărăităreanu (Foods)
The behavior of Listeria monocytogenes (L. monocytogenes) throughout the shelf life of ready-to-eat foodstuffs represents a major concern in relation to human diet and human health. The aim of the study was to evaluate the behavior of L. monocytogenes in Wiener sausage, as an RTE meat product, throughout 15 days of storage (0–7 °C) under the action of fermented juice from parsley (Petroselinum crispum var. tuberosum) roots and common hawthorn (Crataegus monogyna) berry phenolics, compared with the effect of the food additives sodium nitrite and sodium ascorbate used in the standard formulation. For this purpose, one experimental formulation (F1) and one standard formulation (F2) of Wiener sausages were designed using the following preservatives and antioxidants: 50 ppm fermented parsley root juice (as a nitrite source) and 50 ppm hawthorn berry phenolics were used in F1, and 50 ppm sodium nitrite (as food additive E 250) and 50 ppm sodium ascorbate (as food additive E 301) were used in F2. The ability to support L. monocytogenes growth was assessed by a challenge test throughout the 15 days of storage. Based on the results of the assessment, the natural ingredients fermented parsley root juice and hawthorn berry phenolics could act as preservatives that ensure microbiological safety during the shelf life of the product. The nitrite and phenolic compounds of these natural ingredients showed antimicrobial activity against foodborne pathogens, including L. monocytogenes.